Computer-based material management information system in a manufacturing company - Shu, Wen-chieh; Techapun Raengkhum; Pakorn Adulbhan; Sharif, M. N.; Tatung Company, Taiwan (Bangkok : Asian Institute of Technology, 1978)
This study is aimed at designing the materials management information system in a manufacturing company. To visualize the broad range of this information system more realistically, the Tatung Company was chosen to be the example for this study. A general description about the company, including the organization structure, is made first. Then the existing system concerned is investigated in terms of data, documents, and information. Secondly, the users' requirements are surveyed for their specific purposes. Some ideal cases are needed to combine the users' requirements for proposing a new system. Lastly, utilizing the computer in the proposed system is studied. This study is started from the feasibility of computerization, file design, to the system run4 Some alternatives concerned with system design are also discussed. Conclusions and recommendations for future work were made after that.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1978
Keywords: Materials management